Kunūz al-Malik Sulaymān : al-qiṣṣah al-ūlá: Manājim al-Malik Sulaymān - Haggard, H. Rider (Henry Rider), 1856-1925 (World best sellers series., 2015)
An elephant hunter and an English nobleman track the latter's missing brother, who disappeared while searching for King Solomon's legendary lost diamond mines.